Study on progressive collapse mechanism of RC frame structures corroded by chloride - Bao, Chao; Wang, Huxiang; Long, Huan; Alshaikh, Ibrahim M. H.; Al-Gaboby, Ziyad; Ma, Xiaotong (Elsevier, 2025)
An excessive failure mechanism describes the progressive collapse of reinforced concrete (RC) structures, where localized initial damage from abnormal loading cases can lead to either the collapse of a significant component or the entire structure. RC structures in coastal or saline environments face long-term degradation due to environmental corrosive agents, with steel corrosion, which is induced by chloride ingress being a major cause. This study investigates the effect of full-beam corrosion on the progressive collapse behavior of RC frame structures. Therefore, quasi-static loading tests were carried out to examine two 1/3-scale RC substructure specimens. For comparison purposes, one specimen serves as a control specimen and another specimen has been exposed to corrosion treatment using electrochemical methods. The results indicated that the structures resistance mechanism remained unchanged after steel corrosion, but the corroded structure entered the catenary action mechanism earlier. Corrosion weakens the enhancement effects of compression arching and catenary action on the structural resistance, and the yield load, first peak load, and ultimate load of the specimen have all decreased by 4.8?%, 3.2?%, and 43.8?%, respectively. Based on the quasi-static test results, dynamic responses of the two types of specimens were obtained, and collapse resistance assessments were conducted, specimen F14-0 still retained 11?% residual capacity against collapse, while the corroded specimen recorded 6.2?% only, a decrease of nearly 44?%.